The Nature of the Decision-Making Process and two Complementary Frameworks to understand it - درة د. عبد الباري (Dirasat in Economics and Business, 1982)
The paper deals with two central in the decision-making process. The nature of the process and the prescriptive and descriptive frameworks. As to the first issue, the decision-making process is an essential process in the life of any complex organization because it permeates all the managerial subprocesses of planning, organizing, staffing, directing and controlling. On the other hand, the decision-making process is a continuous process in the activities of any manager and an indicator of his success and effectiveness. Furthermore, the decision-making process is a complex one and should be studied on many levels; the individual, the group, the organization and the society. Students of decision-making advocate apparently two conflicting frameworks to study and understand that process. The prescriptive framework addresses it-self to the issue of providing norms and procedures to be followed in order to obtain certain results. This framework is based on three assumptions: First, it assumes that people are economic human beings. Second, it views the decision-maker as one who possesses perfect knowledge and knows the choices, the consequences and payoffs. Finally, it assumes that the decision-maker has an order of preference that allows him to rank the relative desirability of the payoffs. The other framework is the descriptive or behavioral model which is concerned with analyzing the decision-making process without reference to a specific norm or goal. The assumptions of the descriptive frame work are the following : 1.decision-maker is an administrative man. 2. Human beings are unable to acquire perfect knowledge of alternatives, out-comes and payoffs. Their rationality is bounded. 3. The search process is a sequential one. The concept of satisfying advocated by Herbert Simon is a central concept in this theory. The paper concludes with the idea that rationality in decision-making could be achieved through taking into account the two frameworks together. Each has its strengths and draw-backs. A complementary outlook which combines the two frameworks is a sine quae non if we want to understand the decision-making process thoroughly.